Response of soil bacterial communities in wheat rhizosphere to straw mulching and N fertilization - Chen, Songhe; Xiang, Xiaoling; Ma, Hongliang; Penttinen, Petri; Zheng, Ting; Huang, Xiulan; Fan, Gaoqiong (Frontiers in Microbiology, 2022)
Straw mulching and N fertilization are effective in augmenting crop yields. Since their combined effects on wheat rhizosphere bacterial communities remain largely unknown, our aim was to assess how the bacterial communities respond to these agricultural measures. We studied wheat rhizosphere microbiomes in a split-plot design experiment with maize straw mulching (0 and 8000 kg straw ha-1) as the main-plot treatment and N fertilization (0, 120 and 180 kg N ha-1) as the sub-plot treatment. Bacterial communities in the rhizosphere were analyzed using 16S rRNA gene amplicon sequencing and quantitative PCR. Most of the differences in soil physicochemical properties and rhizosphere bacterial communities were detected between the straw mulching (SM) and no straw mulching (NSM) treatments. The contents of soil organic C (SOC), total N (TN), NH4+-N, available N (AN), available P (AP) and available K (AK) were higher with than without mulching. Straw mulching led to greater abundance, diversity and richness of the rhizosphere bacterial communities. The differences in bacterial community composition were related to differences in soil temperature and SOC, AP and AK contents. Straw mulching altered the soil physiochemical properties, leading to greater bacterial diversity and richness of the rhizosphere bacterial communities, likely mostly due to the increase in SOC content that provided an effective C source for the bacteria. The relative abundance of Proteobacteria was high in all treatments and most of the differentially abundant OTUs were proteobacterial. Multiple OTUs assigned to Acidobacteria, Chloroflexi and Actinobacteria were enriched in the SM treatment. Putative plant growth promoters were enriched both in the SM and NSM treatments. These findings indicate potential strategies for the agricultural management of soil microbiomes.